Forecasting surface water level fluctuations of lake Serwy (Northeastern Poland) by artificial neural networks and multiple linear regression - Piasecki, Adam; Jurasz, Jakub; Skowron, Rajmund (Journal of Environmental Engineering and Landscape Management, 2017)
The aim of this study is to assess the possibility of forecasting water level fluctuations in a relatively small (